A case of gastric heterotopic pancreas with gastroduodenal invagination - Shoko Iwahashi; Masaaki Nishi; Toshiaki Yoshimoto; Hideya Kashihara; Chie Takasu; Takuya Tokunaga; Tomohiko Miyatani; Jun Higashijima; Kozo Yoshikawa; Yuma Wada; Yoshimi Bando; Mitsuo Shimada (Surgical Case Reports, 2019)
Abstract Background Heterotopic pancreas (HP) is a rare disease commonly found incidentally on imaging studies, at endoscopy or at autopsy and can be associated with abdominal pain, vomiting, heart burn, gastric outlet obstruction, and even dysphagia in very rare cases. Heinrich’s classified HP into three groups, types1–3, with Heinrich’s type 3 HP the rarest and difficult to diagnose properly because it has only pancreatic ducts but has no islet and acini. The aim of this study is to report a case of gastric outlet obstruction caused by type 3 HP with gastroduodenal invagination with reference to the literature and diagnosed finally by immuno-histochemical analysis. Case presentation The case presented is a 40-year-old male presenting with vomiting and abdominal pain. Computed tomography (CT) revealed a cystic mass in the upper abdomen and he was referred to the Tokushima University. Gastric fiber showed that the pedunculated mass originated from the stomach. An open distal gastrectomy was performed. Pathologically, there was small glands proliferation in the sub-mucosal (SM) layer which was membrane and cytoplasm (MUC)1 positive and muscle proliferation. Results This finding revealed the tumor as HP. Postoperative course was uneventful and the patient was discharged 12 days after surgery. The patient has remained well 12 months after surgery. Conclusions HP should be considered in the differential diagnosis of SM tumors with gastroduodenal invagination even if this is a rare symptom.